Various Strategies Available For Home Automation Prediction Using IoT Learning Techniques - Krishnarajan.S.N, Lakshmi.Dr (International Journal of Advanced Science and Technology, 2020)
Automation is playing an important role in every human’s life. In this current scenario Home Automation is more popular.  Because this system is provides helps to decrease manual efforts and mistakes. Using this automation system the human beings are able to control various electrical home appliances like bulb, TV, AC, fan etc. Home automations system is constructed by using different type of technologies.  The important techniques used in home automation system are Bluetooth, internet radio frequency and remote control.  Each technique has its merits and demerits.  This proposed home automation system is controlled by using IOT. The user can send the control message through their android based phone.  Control message is passed to the home appliances through IOT and Arduino controller. The main purpose of home automation system is to assist elderly people and handicapped as they feel difficult to handle electrical home appliances.